Some methods of fish capture along Agno River, Pangasinan. - Fabiaña, Manuel R. (College of Fisheries, University of the Philippines, 1952)
During the early years, Filipino fishermen used the beach seine to catch fish for home consumption. The methods they employed then were primitive. However, after liberation the beach seine outfit found its modernized counterpart. After a successful demonstrative operation, its use grew to a wide extent to that it soon spread all over. It is not very surprising therefore to see a number of beach seines being operated along the shores of Lingayen Gulf, Manila Bay and in nearly all parts of the Philippine Islands. The chartered waters of the Philippine Islands comprising thousands of big and small islands reveal the great extent of marine resources of our country. Generally, different kinds of fishing gears are used to exploit and utilize these resources. The location of certain islands and the natural characteristics of the different marine species that abound there at are factors which encouraged the fishermen to invent ways and means to effect its exploitation. This report evaluates some methods of fish capture in the conservation of our fishery resources. The knowledge acquired by the fishermen on the operation of these gears is a means of eradicating destructive methods of fishing in our fishing grounds.